A numerical analysis of the transport of modified hybrid nanofluids containing various nanoparticles with mixed convection applications in a vertical cylinder - Riaz, Arshad; Abbasi, A.; Al-Khaled, Kamel; Gulzar, Sidra; Khan, Sami Ullah; Farooq, W.; El-Din, ElSayed M. Tag (Frontiers in Physics, 2022)
The hybrid materials are impressive class of nanofluids with exciting thermal outcomes and present applications in the enhancing the heat transfer procedure, solar energy, extrusion processes and in different engineering processes. Current contribution aims to reflect the improved mechanism of heat transfer phenomenon for hybrid nanofluid. The aluminium oxide, copper and copper oxide at different solid volume fractions are used to report the thermal phenomenon. For base material, water liquid is used. The mixed convection applications are also encountered. The moving cylinder with stretched uniform velocity causes the flow. The velocity slip and convective boundary constraints are used to observe the flow phenomenon. The hybrid nanofluid is expressed via different mathematical relations. The shape factors for hybrid nanomaterials are presented. The Keller Box numerical method with effective accuracy has been entertained for the simulation process. The applications of parameters for current model are explained via graphs.